Mafhum Al-Mutalaazimat Al-Istilahiyyah: Diraasah Tatbiqiyyah fi Mu’jam Al-Mutqin - Husaini, Majid; Ad-Dakheel, Muhammad Majid (Ar Raniry : International Journal of Islamic Studies, 2015)
This study seeks to shed light on the phenomenon of the conventional syndromes as an important mechanism in the generation of meanings and enrich the language graphical card huge, as provided syndromes material language simplified to express accurately the meanings and clarity, and as this phenomenon reflects the state of development in the use of language on the level verbal and moral level was lexical environment is the best place to study them; so was material lexicon (ALmotqan) Rule Applied to search for syndromes idiomatic help to describe the phenomenon studied and according to scientific methodology.